2010
DOI: 10.1073/pnas.0913734107
|View full text |Cite
|
Sign up to set email alerts
|

Membrane curvature controls dynamin polymerization

Abstract: The generation of membrane curvature in intracellular traffic involves many proteins that can curve lipid bilayers. Among these, dynamin-like proteins were shown to deform membranes into tubules, and thus far are the only proteins known to mechanically drive membrane fission. Because dynamin forms a helical coat circling a membrane tubule, its polymerization is thought to be responsible for this membrane deformation. Here we show that the force generated by dynamin polymerization, 18 pN, is sufficient to defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
278
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(298 citation statements)
references
References 41 publications
16
278
3
1
Order By: Relevance
“…2B). These results show that Drp1 has no preference for binding to curved or flat membranes, in contrast to what has been reported for other dynamins (48). In general, the distribution of the protein was mostly homogeneous on the membrane surface (Fig.…”
Section: Drp1 Binds To Both Flat and Curved Membranes In Absence Ofcontrasting
confidence: 47%
“…2B). These results show that Drp1 has no preference for binding to curved or flat membranes, in contrast to what has been reported for other dynamins (48). In general, the distribution of the protein was mostly homogeneous on the membrane surface (Fig.…”
Section: Drp1 Binds To Both Flat and Curved Membranes In Absence Ofcontrasting
confidence: 47%
“…For interaction with outer plasma membrane mechanotransducer ion channels, other dynaminlike proteins are not very suitable targets (46,47). We believe that the most striking aspect of dynasore's action-potentiation of lowdose GsMTx4-are rooted in the known effect of dynamin on membrane curvature (66,67). Dynamin, also referred to as mechanochemical GTPase (68), according to this interpretation, could contribute to lack of effect at lower doses of GsMTx4, by its link to membrane curvature so that GsMTx4 peptide could not insert itself in a very efficient way at the channel-lipid interface to inhibit PIEZO1/2 in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Curved surfaces resulting from fluctuations in the low tension membrane reservoir present on SUPER templates in vitro or those generated by other mechanisms in vivo might serve as membrane templates capable of activating and recruiting N-BAR domain-containing EAPs (54). Others have suggested that the curvature sensing and generating activities of dynamin and N-BAR domains can create positive feedback loops to enhance membrane tubulation (55).…”
Section: Discussionmentioning
confidence: 99%